Hypothermia and neonatal morbimortality in very low birth weight preterm infants - Rafaelle Cristine Oliveira Cordeiro; Daniela Marques de Lima Mota Ferreira; Heloísio dos Reis; Vivian Mara Gonçalves de Oliveira Azevedo; Airan dos Santos Protázio; Vânia Olivetti Steffen Abdallah (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To assess the prevalence of hypothermia in the delivery room, at admission, and 2 to 3 hours after admission in the neonatal intensive care unit (NICU), factors associated and possible relationship with morbidity and mortality in preterm infants with very low birth weight (VLBW). Methods: Cross-sectional study with data collection based on a retrospective review of medical records and including infants born in 2016 and 2017, with birth weights <1500g, and gestational ages <34 weeks. Data about VLBW preterm infants, maternal data and temperature in the delivery room were analyzed. Hypothermia was considered when axillary temperature <36°C. For statistical analysis, the chi-square test or G test, canonical and Spearman correlation, and logistic regression were used. Results: 149 newborns (NB) were included in the study. The prevalence of hypothermia in delivery room, at admission to the NICU and 2 to 3 hours after admission was 25.8%, 41.5% and 40.2%, respectively. The temperature of NBs was directly proportional to gestational age (p<0.010), birth weight (p<0.010), and Apgar score (p<0.050). There was an inverse association with hypothermia in the delivery room and cesarean delivery (OR 0.25; p=0.016). Conclusions: Hypothermia was a prevalent problem in the studied population. The neonatal temperature was directly proportional to gestational age, birth weight and Apgar score. Hypothermia was associated with maternal factors, such as cesarean delivery. It is necessary to implement and improve strategies for its prevention.